A comprehensive review of tyre wear particles: Formation, measurements, properties, and influencing factors. (15th March 2023) - Zhang, Mengzhu; Yin, Hang; Tan, Jianwei; Wang, Xin; Yang, Zhengjun; Hao, Lijun; Du, Tianqiang; Niu, Zhihui; Ge, Yunshan
Abstract: With the implementation of stringent emission regulations and the growth of electric vehicles, more attention should be shifted to road traffic-derived non-exhaust emissions. Tyre wear particle (TWP) emissions have outweighed those from the exhaust and are potential for microplastic pollution. However, there are no regulations that specifically limit TWP emissions and no feasible technologies to curb the emissions. Due to the varied measurements and discrepant data, the related results are incomparable and uncertain. This paper gives a comprehensive overview of TWP from four aspects: formation mechanisms, experimental methods, emission characteristics, and influencing factors. Real-road TWP are generally incorporated with existing road particles, so the sampling methods need to be carefully designed to eliminate the influence of undesired particles. In this case, the TWP scattering paths, the effects of sampling flow rate and sampling inlet location, the design principles of sampling geometry based on sampling flow rate and vehicle speed are discussed. The micro-vibration and the stick-slip oscillation between the tyre and road, coupled with the evaporation of tread volatile compounds, lead to the TWP formation. Thus, TWP covers a broader size distribution, diverse shapes, and multiple chemical components. Further studies should be focused on the physicochemical properties of TWP by standardizing experimental procedures and narrow controlling the main influencing factors of vehicle driving behaviours, road types, tyre specifications, and the ambient environment. Highlights: TWP sampling, analysis, and parameters affecting the efficiency are summarized. TWP formation, scattering path, emission, and physicochemical property are compared. Effects of major influencing factors of driving and environment are discussed.